Religious Culture of Sharia Microfinance Institutions in Denpasar-Bali - Siswanto Siswanto; Khairil Anwar (UIN Maulana Malik Ibrahim Malang, 2020)
This study aims to develop organizational culture in Islamic microfinance institutions Baitul Maal wa at-Tamwil (BMT) Sidogiri in Denpasar, Bali. Organizational culture is a basic assumption that grows from social construction results based on a mutual agreement to solve problems and achieve organizational goals. Therefore, the organizational culture in each company is different. This study uses a qualitative approach to data collection and analysis. Data collection uses in-depth interviews with the informant. The informants are leaders, employees, and customers of the BMT. The results of the study show the practice of religious culture. The dimensions of religious culture are amanah or trustworthy, mutual help (ta'awun), kinship and togetherness. Its value is clarified with sharia enterprise theory. This research has implications for developing the concept of organizational culture based on the peculiarities of Islamic microfinance institutions based on pesantren. Penelitian ini memiliki tujuan untuk mengembangkan konsep budaya organisasi di lembaga keuangan mikro syariah BMT Sidogiri Denpasar, Bali. Budaya organisasi merupakan asumsi dasar yang tumbuh dari hasil konstruksi sosial berdasarkan kesepakatan bersama untuk menyelesaikan masalah dan mencapai tujuan organisasi. Oleh karena itu, budaya organisasi dalam setiap perusahaan berbeda-beda. Penelitian ini menggunakan pendekatan kualitatif dalam pengumpulan dan analisis data. Pengumpulan data menggunakan wawancara mendalam kepada informan. Para informan adalah pimpinan, karyawan, dan nasabah BMT Sidogiri. Hasil penelitian menemukan penerapan budaya religius. Dimensi budaya religius tersebut meliputi amanah, tolong menolong (ta’awun), kekeluargaan kebersamaan. Nilai budaya religius tersebut selanjutnya diperjelas dengan teori usaha syariah. Penelitian ini memiliki implikasi pada pengembangan konsep budaya organisasi berdasarkan kekhasan lembaga keuangan mikro syariah berbasis pesantren.